KAJIAN COVID-19 PADA BIDANG SAINS INFORMASI DAN KEPUSTAKAAN - Testiani Makmur; Depi Suadi; Dafrizal Samsudin (Publication Library and Information Science, 2021)
The purpose of this study is to see trends in Covid-19 studies related to the field of information science and literature published by domestic and foreign researchers. Using the literature study method by searching indexed documents on the portals of Google Scholar, GARUDA, ResearchGate and Sinta. This research found 34 scientific articles on the theme of Covid-19 related to the fields of information science and literature. 10 countries publish and publish overseas researchers. There are 7 topics studied, including library services and innovation in the Covid-19 era, librarians, librarian hopes for the Covid-19 period, virtual and literacy, Covid-19 information on library sites, library policies for Covid-19 and the future of libraries after Covid-19. In this study it can be ignored (1) there are not many fields of Information Science and libraries related to Covid-19, when compared to the disciplines of education, law and health. (2) Not all countries in the world have checked it. (3) Of the many domestic scientific journals in the field of Information Science and libraries, only 13 journals have published them. (3) Some domestic researchers conducted field studies and literature studies were more dominant. (4) On average, domestic researchers review library services. Interestingly, the services discussed were limited to university libraries and none of them studied school libraries.